2020
DOI: 10.3390/su12030796
|View full text |Cite
|
Sign up to set email alerts
|

A University Training Programme for Acquiring Entrepreneurial and Transversal Employability Skills, a Students’ Assessment

Abstract: The objective of this paper is to analyze university graduate students’ assessments of the attainment of skills acquired in a Training Programme (TP) to develop entrepreneurial skills and transversal employability competencies. Both are vital for the success of today’s societies and play an important role in the sustainable development agenda. The TP was a 12-week programme with six modules combining entrepreneurship training and traditional teaching methods. There were nine editions and 148 students worked in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 58 publications
0
31
0
Order By: Relevance
“…Pardo-García and Barac (2020) [22] found that an innovative training itinerary is an opportunity to develop students' creativity and entrepreneurship to create something from zero, being proactive, and solving a need that exists in the society. The methodologies used to measure the efficiency of entrepreneurial education programs are mainly focused on three areas: entrepreneurial intention, entrepreneurial activity, and acquired skills [23]. Empirical studies have found that there is a significant relationship between students' behavior and students' access to entrepreneurship education.…”
Section: Entrepreneurship Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Pardo-García and Barac (2020) [22] found that an innovative training itinerary is an opportunity to develop students' creativity and entrepreneurship to create something from zero, being proactive, and solving a need that exists in the society. The methodologies used to measure the efficiency of entrepreneurial education programs are mainly focused on three areas: entrepreneurial intention, entrepreneurial activity, and acquired skills [23]. Empirical studies have found that there is a significant relationship between students' behavior and students' access to entrepreneurship education.…”
Section: Entrepreneurship Educationmentioning
confidence: 99%
“…They found that entrepreneurship education had greatly improved college students' business knowledge and skills, and significantly increased their engagement in small businesses after graduation [26][27][28][29]. Laguna-Sánchez et al (2020) [23] found that the students attained two types of skills, acquiring a higher level of proficiency in entrepreneurial skills, as well as transversal competencies through training programs. Some other studies also indicate strong correlations between student participation in entrepreneurship education and the formation of their entrepreneurial intention [6,[30][31][32].…”
Section: Entrepreneurship Educationmentioning
confidence: 99%
“…Evidence from contemporary literature suggests that Soft Skill Attributes contribute to the sustainable employment of the business graduates significantly [70]. Furtherance by higher education institutions of measures in line with labor market demands enables students to acquire skills and capacities that prepare them for working life and enhance their employability, in line with what was expressed by Laguna-Sánchez et al [71]. This study explored the importance of creativity and team working measured in terms of academic results and student satisfaction.…”
Section: Discussionmentioning
confidence: 72%
“…The students themselves could be the best referees to assess the achievement of the competences and it seems essential to include their perceptions relating to the goals for the teaching-learning process defined by teaching plans [22][23][24][25]. The loss of communication between students and other stakeholders linked to the education system, such as lecturers but also the institutions themselves, can create gaps that decrease the accuracy of defining competence goals.…”
Section: Introductionmentioning
confidence: 99%